Reptilia, Squamata, Viperidae, Bothrops venezuelensis Leybold, 1873: Distribution extension and first country record - Juan Mendoza; Viviana Berrio; Diego Gómez (Check List, 2012)
We report on the presence of Bothrops venezuelensis Leybold, 1873 in Norte de Santander and Boyacá departments, Colombia. These findings represent the first records for the country. Extending the species’ distribution 474 km in a straight-line distance SW from its nearest previously known Venezuelan locality. The present record adds a new clinically important species for Colombia, which needs to be considered in the production of anti-ophidic serum.